Decreased prevalence of moderate to severe COPD over 15 years in northern Sweden. (May 2016) - Backman, Helena; Eriksson, Berne; Rönmark, Eva; Hedman, Linnea; Stridsman, Caroline; Jansson, Sven-Arne; Lindberg, Anne; Lundbäck, Bo
Abstract: Background: The burden of COPD in terms of mortality, morbidity, costs and prevalence has increased worldwide. Recent results on prevalence in Western Europe are conflicting. In Sweden smoking prevalence has steadily decreased over the past 30 years. Aim: The aim was to study changes in prevalence and risk factor patterns of COPD in the same area and within the same age-span 15 years apart. Material and methods: Two population-based cross-sectional samples in ages 23–72 years participating at examinations in 1994 and 2009, respectively, were compared in terms of COPD prevalence, severity and risk factor patterns. Two different definitions of COPD were used; FEV1 /FVC < LLN and FEV1 /FVC < 0.7. The severity of COPD was assessed by FEV1, both as % of predicted and in relation to the LLN. Results: The prevalence of COPD decreased significantly from 9.5% to 6.3% (p = 0.030) according to the FEV1/FVC < LLN criterion, while the decrease based on the FEV1 /FVC < 0.7 criterion from 10.5% to 8.5% was non-significant. The prevalence of moderate to severe COPD decreased substantially and significantly, and the risk factor pattern was altered in 2009 when, beside age and smoking, also socio-economic status based on occupation was significantly associated with COPD. Conclusions: Changes in both prevalence and risk factor patterns of COPD were observed between surveys. Following a continuing decrease in smoking habits over several decades, a decrease in the prevalence of moderate to severe COPD was observed from 1994 to 2009 in northern Sweden. Highlights: The prevalence of moderate to severe COPD has decreased in northern Sweden from 1994 to 2009. The decrease appears after more than three decades of decreasing smoking prevalence in the area. The risk factor pattern for COPD was altered in 2009, probably at least partly due to the decreased smoking habits.